2021
DOI: 10.29312/remexca.v0i26.2946
|View full text |Cite
|
Sign up to set email alerts
|

Nanopartículas de selenio absorbidas en hidrogeles de quitosán-polivinil alcohol en la producción de pepino injertado

Abstract: En la búsqueda por mejorar el uso de los recursos naturales y aumentar el rendimiento y la calidad de los frutos empleando técnicas amigables con el medio ambiente, como el injerto y el uso de nanopartículas metálicas. El objetivo de este trabajo fue determinar el efecto del injerto combinado con la aplicación de diferentes concentraciones de nanopartículas de selenio (Se NPs) encapsuladas en un gramo del hidrogel de quitosán-polivinil alcohol (CS-PVA) en la productividad y producción de pepino injertado. Los … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Regarding the factors evaluated, the results obtained in this study (Table 1) showed an increase in each of the variables that differentiate the two factors of grafted tomato plants versus non-grafted tomato plants, as well as in plant height, number of leaves, number of fruits, fruits' weight, and equatorial and polar diameters of the fruit, because a grafted plant is more efficient in the absorption and transport of water and ions from the root to the other organs, increasing the accumulation of biomass [16]. Treviño López [17] found that the effect of grafting has a positive effect on production variables, such as an increase in fruit diameter and weight compared to plants without grafting. Similar results to those of a research work where they reported an increase in fruit length, number of fruits, and yield per plant, the highest values were obtained in fruits of grafted plants [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the factors evaluated, the results obtained in this study (Table 1) showed an increase in each of the variables that differentiate the two factors of grafted tomato plants versus non-grafted tomato plants, as well as in plant height, number of leaves, number of fruits, fruits' weight, and equatorial and polar diameters of the fruit, because a grafted plant is more efficient in the absorption and transport of water and ions from the root to the other organs, increasing the accumulation of biomass [16]. Treviño López [17] found that the effect of grafting has a positive effect on production variables, such as an increase in fruit diameter and weight compared to plants without grafting. Similar results to those of a research work where they reported an increase in fruit length, number of fruits, and yield per plant, the highest values were obtained in fruits of grafted plants [4].…”
Section: Discussionmentioning
confidence: 99%
“…The grafts increased the values of the agronomic variables, with higher values in variables such as leaf area. It may be said that the leaf area and height of the plant, which resulted in an increase of 0.96% in this variable, is reflected in a yield of 38% compared to the control [17]. A study shows that tomato fruits from grafted plants with Multifort/CID modified the mineral composition and improved yield [8].…”
Section: Discussionmentioning
confidence: 99%
“…This combined approach holds the potential to mitigate the adverse impacts of Cd stress on plant growth and health, thereby contributing to sustainable agricultural practices and environmental protection [23]. Additionally, humic acid's capacity to enhance nutrient uptake and promote root development could synergistically support selenium's role in bolstering antioxidant defense mechanisms and detoxification pathways within plants [24]. However, there are a few reports about the participation of the combined effect of humic acid and Se in the mitigation of Cd stress in terms of biochemical traits in chili plants.…”
Section: Of 16mentioning
confidence: 99%
“…According to the supplier, the Se NPs were of a spherical morphology, with a size range of 2-20 nm, determined by transmission electron microscopy (TEM). González-García et al [28] and Treviño-López et al [29] provided complete characterizations. We synthesized the ZnO NPs according to the procedure reported by Garza-Alonso et al [30], and they had a quasi-spherical shape and an average particle size of 16.49 nm, as determined by TEM.…”
Section: Reagentsmentioning
confidence: 99%